FBG-Based UV-Curing Kinetics Analysis by Exothermic Behavior - Wen Yan; Zhenhua Bi; Ying Song; Xinpu Zhang (Photonic Sensors)
Abstract Since photo-induced polymerization of the ultra-violet (UV)-curing adhesive from a fluid state to a solid state is an exothermic process, the UV curing exothermic behavior can be regarded as a potential evaluation methodology to analyze UV-curing kinetics. Herein, a fiber Bragg grating (FBG)-based UV curing exothermic behavior monitoring is proposed to evaluate the UV-curing dynamic process and analyze a series of thermal and mechanical properties changes during curing. The exothermic behavior of the UV curing adhesive during curing and the feasibility of FBG-based curing kinetic analysis scheme are verified experimentally, full cycle cure monitoring of the UV curing adhesive can be realized by this FBG-based curing kinetic analysis scheme, and the UV-curing kinetics of four different types of the UV curing adhesive are corresponding to different exothermic behaviors. Compared with curing process evaluation based on refractive index variation, this FBG-based exothermic behavior monitoring has the ability to extract more details of the curing process, and some curing stages with negligible refractive index changes also can be distinguished. By using this proposed scheme, the UV-curing dynamic process and multiple characteristic parameters, such as curing time, time constant, transient temperature rise, and residual stress, can be evaluated, which may contribute to evaluating and analyzing UV-curing kinetics more comprehensively.